2021
DOI: 10.1113/jp281752
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of muscle and mitochondrial health by the mitochondrial fission protein Drp1 in aged mice

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…33 For example, genetic ablation or overexpression of DRP1, the primary mediator of mitochondrial fission, impairs skeletal muscle integrity, induces muscle wasting, and diminishes metabolic control throughout the lifespan. 34,35 We found that BAM15 reduced mitochondrial fission in aged muscle indirectly by lowering expression of MiD49/51 and FIS1, the proteins responsible for DRP1 binding and docking on the outer mitochondrial membrane. 36 Importantly, restricting receptor/adaptor activity prevents excessive fission and generation of dysfunctional mitochondria while allowing routine fission to occur.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…33 For example, genetic ablation or overexpression of DRP1, the primary mediator of mitochondrial fission, impairs skeletal muscle integrity, induces muscle wasting, and diminishes metabolic control throughout the lifespan. 34,35 We found that BAM15 reduced mitochondrial fission in aged muscle indirectly by lowering expression of MiD49/51 and FIS1, the proteins responsible for DRP1 binding and docking on the outer mitochondrial membrane. 36 Importantly, restricting receptor/adaptor activity prevents excessive fission and generation of dysfunctional mitochondria while allowing routine fission to occur.…”
Section: Discussionmentioning
confidence: 81%
“…Mitochondria are dynamic organelles, whose morphology and function are regulated through continuous balancing of fission and fusion processes 33 . For example, genetic ablation or overexpression of DRP1, the primary mediator of mitochondrial fission, impairs skeletal muscle integrity, induces muscle wasting, and diminishes metabolic control throughout the lifespan 34,35 . We found that BAM15 reduced mitochondrial fission in aged muscle indirectly by lowering expression of MiD49/51 and FIS1, the proteins responsible for DRP1 binding and docking on the outer mitochondrial membrane 36 .…”
Section: Discussionmentioning
confidence: 86%
“…Aged mice demonstrate reduced DRP1 activity and alterations in mitochondrial morphology in several tissues, including skeletal muscle, neurons, and oocytes 75,76 . Interestingly, both muscle-specific DRP1 overexpression or DRP1 knockdown in 18-month-old mice causes muscle atrophy 77 . Recently, it has been shown that the RNA-binding protein pumilio 2 (PUM2) increases with age in worms, mice, and humans 67 .…”
Section: Box 1 | Epigenetic Modulations In Response To Mitochondrial ...mentioning
confidence: 99%
“…Our previous work suggests that loss of SIRT1, an important regulator of mitochondrial biogenesis via activation of protein peroxisome proliferator-activated receptor-gamma coactivator 1α (PGC1α) 15 in MSCs, reduces the restoration of muscle function after an injury. 16 Further, reducing mitochondrial biogenesis and Drp1 expression increases fibrosis, 17,18 while reducing mitochondria-induced ROS accumulation can lower muscle fibrosis. 19 Because reducing PGC1α-regulated mitochondrial biogenesis can inhibit muscle repair, we hypothesized that increasing functional mitochondria in injured muscle would reduce muscle fibrosis and improve restoration of muscle function.…”
Section: Introductionmentioning
confidence: 99%